2021
DOI: 10.3389/fonc.2021.641931
|View full text |Cite
|
Sign up to set email alerts
|

DCTPP1, an Oncogene Regulated by miR-378a-3p, Promotes Proliferation of Breast Cancer via DNA Repair Signaling Pathway

Abstract: Breast cancer (BRCA) is one of the most deadly cancers worldwide, with poor survival rates that could be due to its high proliferation. Human all-alpha dCTP pyrophosphatase 1 (DCTPP1) is implicated in numerous diseases, including cancers. However, its role in BRCA is unclear. In this study, we used bioinformatic analyses of the ONCOMINE, UALCAN, and GEPIA databases to determine the expression pattern of DCTPP1 in BRCA. We found that elevated DCTPP1 levels correlate with poor BRCA prognosis. DCTPP1 silencing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…First, we used lentivirus to deliver shRNA targeting DCTPP1 to construct the DCTPPI knockdown cell model of ovarian cancer cells. Through the cell models, we have observed that DCTPP1 is a promoter for the growth of ovarian cancer, which is consistent with the finding in prostate cancer and gastric cancer ( Marquard and Jucker, 2020 ; Niu et al, 2021 ). With DCTPP1 knockdown, ovarian cancer cells showed growth inhibition both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…First, we used lentivirus to deliver shRNA targeting DCTPP1 to construct the DCTPPI knockdown cell model of ovarian cancer cells. Through the cell models, we have observed that DCTPP1 is a promoter for the growth of ovarian cancer, which is consistent with the finding in prostate cancer and gastric cancer ( Marquard and Jucker, 2020 ; Niu et al, 2021 ). With DCTPP1 knockdown, ovarian cancer cells showed growth inhibition both in vivo and in vitro .…”
Section: Discussionsupporting
confidence: 87%
“…DCTTP1 exhibits nucleic accumulation in multiple carcinomas ( Requena et al, 2014 ; Requena et al, 2016 ). Researches have shown that DCTPP1 promotes proliferation of breast cancer via DNA repair signaling pathway ( Requena et al, 2016 ; Xia et al, 2016 ; Niu et al, 2021 ). Recently, the regulatory function of DCTPP1 in drug response has gained attraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, HMGB3 is also a prototypical marker of breast cancer progression but worsens cancer progression primarily by promoting formation of breast layers of breast cancer cells [ 40 , 41 ]. DCTPP1 is an oncogene regulated by the oncogenic factor miR-378a-3p, and this gene facilitates breast cancer cell proliferation through the interference of DNA repair signaling pathway [ 42 , 43 ]. The phenomenon of overexpression of SHCBP1 in breast cancer has been studied, and cellular experiments have demonstrated that this gene directly regulates breast cancer cell proliferation and promotes the cell cycle [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main treatments for BC are surgery with adjuvant radiation therapy and chemotherapy [14][15][16][17][18]. However, many BC patients are resistant to chemotherapy, endocrine, and targeted therapy, and these patients generally have poor survival rates [6,[19][20][21][22][23][24]. The complexity and high heterogeneity of the underlying mechanisms of BC make its treatment difficult [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%